Photoemission of 4f and 5f systems - Guziewicz, Elżbieta (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
Photoemission studies provide an extensive insight into the electronic structure and are crucial for comprehension of the wide range of ground state properties found in lanthanide and actinide materials. This paper reviews different techniques used in photoemission experiments with respect to investigation of such specific aspects of the electronic structure of 4f and 5f systems as mixed valence, localization of 4f electron shell, and dual character of the 5f electrons. Photoemission results on lanthanide and actinide systems are also presented.
Optica Applicata, Vol. 36, 2006, nr 2-3, s. 321-338
Keywords: optyka; photoemission spectroscopy; actinides; lanthanides; correlated electron systems